The concentration of Mn and Fe metals in water and sediment of the Sanga-Sanga River, East Kalimantan Province - Larissa, Astrid Attha; Ghitarina, Ghitarina; Hamdhani, Hamdhani (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
This study aimed to analyze the concentrations of manganese (Mn) and iron (Fe) in both water and sediment samples from the Sanga-Sanga River, Kutai Kartanegara Regency, East Kalimantan Province. The research was conducted from October to December 2024 at three stations representing the upstream, midstream, and downstream sections of the river. Sampling was performed using a purposive method based on site characteristics, and analyses were carried out both in situ and at the Water Quality Laboratory, Faculty of Fisheries and Marine Science, Mulawarman University. The concentrations of Mn and Fe were compared with the Indonesian river water quality standard (Government Regulation No. 22 of 2021) and sediment quality guidelines established by the Australian and New Zealand Environment and Conservation Council (ANZECC, 2000). The results showed that Mn concentrations in river water ranged from 0.325 to 1.181 mg/L, exceeding the permissible limit of 0.1 mg/L, while Fe concentrations ranged from 0.3475 to 0.468 mg/L, surpassing the standard of 0.3 mg/L. In sediments, Mn concentrations ranged from 42.38 to 964.47 mg/kg and Fe concentrations from 11,341.23 to 50,344.72 mg/kg, with several stations exceeding the ANZECC guideline limits. Higher concentrations were generally found at midstream and downstream stations, particularly in areas influenced by coal mining, barge transport, and ship repair activities. These findings indicate that the Sanga-Sanga River has experienced notable contamination by Mn and Fe, primarily due to anthropogenic activities related to coal industry operations. Continuous monitoring, stricter waste management, and the implementation of pollution control measures are recommended to prevent further environmental degradation and protect aquatic ecosystems.